Highly Sensitive and Selective Detection of Dopamine Using One-Pot Synthesized Highly Photoluminescent Silicon Nanoparticles - Zhang, Xiaodong; Chen, Xiaokai; Kai, Siqi; Wang, Hong-Yin; Yang, Jingjing; Wu, Fu-Gen; Chen, Zhan (Analytical chemistry (Washington), 2015)
A simple and highly efficient method for dopamine (DA) detection using water-soluble silicon nanoparticles (SiNPs) was reported. The SiNPs with a high quantum yield of 23.6% were synthesized by using a one-pot microwave-assisted method. The fluorescence quenching capability of a variety of molecules on the synthesized SiNPs has been tested; only DA molecules were found to be able to quench the fluorescence of these SiNPs effectively. Therefore, such a quenching effect can be used to selectively detect DA. All other molecules tested have little interference with the dopamine detection, including ascorbic acid, which commonly exists in cells and can possibly affect the dopamine detection. The ratio of the fluorescence intensity difference between the quenched and unquenched cases versus the fluorescence intensity without quenching (ΔI/I) was observed to be linearly proportional to the DA analyte concentration in the range from 0.005 to 10.0 μM, with a detection limit of 0.3 nM (S/N = 3). To the best of our knowledge, this is the lowest limit for DA detection reported so far. The mechanism of fluorescence quenching is attributed to the energy transfer from the SiNPs to the oxidized dopamine molecules through Förster resonance energy transfer. The reported method of SiNP synthesis is very simple and cheap, making the above sensitive and selective DA detection approach using SiNPs practical for many applications.